2021
DOI: 10.1016/j.euo.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Androgen Receptor for Prognosis and Treatment Selection in Prostate Cancer

Abstract: Analysis of androgen receptor (AR) status, particularly AR copy number, in plasma DNA is a minimally invasive method with the potential to identify treatment resistance in patients with castration-resistant prostate cancer (CRPC) starting enzalutamide or abiraterone. Patients with elevated plasma AR do not have worse outcomes than patients with normal plasma AR when treated with taxanes. Consequently, circulating AR may improve clinical decision-making between AR-directed therapies versus taxanes and probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…growth, differentiation and malignant transformation of prostate epithelial cells, which is closely related to the occurrence and development of PCa (24)(25)(26). At present, AR is involved in the proliferation, differentiation, invasion, metastasis and immune escape of PCa (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…growth, differentiation and malignant transformation of prostate epithelial cells, which is closely related to the occurrence and development of PCa (24)(25)(26). At present, AR is involved in the proliferation, differentiation, invasion, metastasis and immune escape of PCa (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Second, unlike the PROfound trial, we used the ctDNA rather than tumor tissue to identify HRR genotyping. However, HRR gene status was found to be concordant between serial ctDNA‐positive sample collected in the mCRPC setting and archival primary tissue taken at cancer diagnosis [ 41 , 42 ]. In addition, the ctDNA% in our cohort was low due to the low PSA level at enrolment.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account preliminary data and previous studies in mCRPC patients, we estimated a 30% prevalence of AR alterations. 17 , 18 Using these parameters, the power analysis identified that a total sample size of 40 patients and 40 events (death) would be required to achieve adequate statistical power. 19 , 20 …”
Section: Methodsmentioning
confidence: 99%